Use of mobile applications in dermatology - Feroze Kaliyadan; Karalikkattil T Ashique (Wolters Kluwer Medknow Publications, 2020)
Smartphones and applications related to the same are ubiquitous now. As dermatologists, we have a wide array of smartphone apps at our disposal which we can use to improve our practice in all aspects-clinical, academic, research, and administrative. This article provides an overview of available apps, tips on using apps-both general and specific for dermatology, as well as discusses the scientific validity of some of these apps and the future of smartphone apps in the context of dermatology.